The Effect Of Budget Planning, Human Resource Competence And Organizational Commitment On Budget Absorption In The North Sumatera Regional Police Satker - Dion Sofianto Purba; Eka Nurmala Sari (Universitas Islam Bandung, 2022)
The purpose of this research is basically to be able to find out, test and analyze the effect of budget planning, human resource competence, organizational commitment to budget absorption in the North Sumatra Regional Police. The research used a qualitative descriptive method with a survey approach. Meanwhile, the data analysis used the SEM-PLS approach. The research findings resulted : First, budget planning does not have a significant effect on budget absorption in the North Sumatra Regional Police. Second, the competence of human resources does not have a significant effect on budget absorption in the North Sumatra Regional Police. Third, organizational commitment has a significant effect on budget absorption in the North Sumatra Regional Police.